(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2021)
Steam gasification of weathered (deposit overlay) and energy (depth of ≥300 m) coal samples of Tavantolgoi deposit situated in Tsogttsetsii soum, Umnugovi aimag were performed in this study. Relationship between coal inherent minerals and catalysts (Fe, Na, binary Fe-Na) in the gasification was investigated in a flow of Ar and steam (1:1) mixture with a rate of 200ml/min at temperature of 800°C for 1h using a fixed bed stainless reactor. Conversion of organic matter was 81.8% for the weathered coal sample, and 21.5% for the energy coal sample during non-catalytic gasification of Tavantolgoi coal. Large amount of inherent calcium minerals included in the weathered coal showed a catalytic effect on gasification activity. However, these minerals reacted actively with sodium catalysts (Na or binary Na-Fe) in stages of pyrolysis and gasification, consequently the catalysts lost their activities. Moreover, Fe ore did not have influence of catalyst in steam gasification of both weathered and energy coal samples. Moreover, an inherent Ca content of the energy coal sample was 10 times smaller than that of weathered coal sample. Gasification activity of the energy coal increased significantly with Na catalyst, and the amount of syngas increased 4.6 times compared to that evolved in noncatalytic gasification of the energy coal. Тавантолгой ордын нүүрсний натри, төмөр катализатортай хийжүүлэлтийн идэвхэд эх эрдсийн үзүүлэх нөлөө Хураангуй: Энэхүү судалгааны ажлаар Өмнөговь аймгийн Цогтцэций сумын нутагт орших Тавантолгойн ордын овоолгын исэлдсэн нүүрс болон 300 метрээс доош гүнд байрлах эрчим хүчний чулуун нүүрсний хийжүүлэлтийн идэвхэд эх эрдсүүдийн нөлөө, мөн Fe, Na болон хосолсон Fe+Na катализаторуудын үзүүлэх нөлөөг тодорхойлох туршилтыг хийж гүйцэтгэв. Тавантолгойн ордын чулуун нүүрсний уурын хийжүүлэлтийн идэвхийн туршилтыг хөдөлгөөнгүй үет ган реакторт, 800ºС температурт, 200 мл/мин урсгал хурдтай аргон хий ба усны уурын 1:1 молийн харьцаа бүхий хийн холимогоор 1 цагийн турш хийжүүлсэн. Катализаторгүй үед Тавантолгойн исэлдсэн нүүрсний органик массын хувирал нь 81.8%, эрчим хүчний нүүрснийх 21.5% байв. Исэлдсэн нүүрсэнд агуулагдах кальци эрдэс нь нүүрсний уурын хийжүүлэлтийн идэвхийг нэмэгдүүлж байсан. Fe катализатор нь Тавантолгойн нүүрсний органик массын хувирлыг 0.32-1.81%-иар л нэмэгдүүлсэн, дан Na ба Fe+Na хосолсон катализатор нь органик массын хувирлыг 18.5-74.3% эрс нэмэгдүүлсэн. Тавантолгойн исэлдсэн нүүрсэнд катализатор хэрэглэх үед нүүрсэнд агуулагдах кальци нь катализатортай урвалд орж хийжүүлэлтийн идэвхэд мэдэгдэхүйц нөлөө үзүүлээгүй. Харин эрдсийн агуулга багатай эрчим хүчний нүүрсэнд кальци нь 10 дахин бага байсан. Эрчим хүчний нүүрсэнд Na катализаторыг хэрэглэх үед эх төмөр эрдэстэй хам идэвхжүүлэлтийн нөлөөгөөр хийжүүлэлтийн урвалын хурдыг эрс нэмэгдүүлсэн. Түлхүүр үг: Нүүрсний эрдэс, уурын хийжүүлэлт, төмрийн хүдэр, натрийн карбонат катализатор.